Calvin is trying to write a perfect cube as the difference of 2 perfect squares. He notices that
1 3 2 3 3 3 4 3 ⋮ = = = = 1 2 3 2 6 2 1 0 2 − − − − ⋮ 0 2 1 2 3 2 6 2
If he continues this pattern, he guesses that 7 3 = a 2 − b 2 . What is a × b ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice observation that one of the square numbers is used in the next.
Are there any other patterns that we can see? What can we say about the general case?
Log in to reply
Can it be that the pattern is : We start with a number 'n' ,then the progression is: n+1 i.e the difference between between a & b increases like 2,3,4....?
I thought about the following lines:
1^3=(1-0)(1+0)=1 1 2^3=(3-1)(3+1)=2 4=2 2^2 3^3=3 3^2 or 7^3=7*7^2 a-b=7 and a+b=49. I get a negative b though.
It's easy. Numbers are there with sums of n^2 and differences of n(using the formula (a+b)(a-b)). Now the numbers with sum of 49 and difference of 7 are 21 and 28. Simply calculating their product is 558.
First notice the pattern. Starting with the 2nd equation, you can see that the b 2 component is the a 2 component from the previous equation. Furthermore, the difference between a and b increases by 1 each time, and, in fact, it is equal the base of the cube root.
1 3 = 1 2 − 0 2 : a - b = 1 = base, 2 3 = 3 2 − 1 2 : a - b = 2 = base, 3 3 = 6 2 − 3 2 : a - b = 3 = base, ....ect.
Following this pattern we eventually come to
7 3 = 2 8 2 − 2 1 2 and therefore a × b = 5 8 8
Upon further study, there is also a pattern for a and b. They follow the pattern of triangular numbers, a ( n ) = 2 n ⋅ ( n + 1 ) . Using this we can generalize the form and we should be able to come up with the equality for any perfect cube with base c.
c 3 = a 2 − b 2
where a = 2 c ⋅ ( c + 1 ) or b + c
and b = 2 c ⋅ ( c − 1 ) .
Log in to reply
Indeed. Once can prove it, by showing that
n 3 = ( 2 n ( n + 1 ) ) 2 − ( 2 ( n − 1 ) n ) 2 .
7 7 7=334 then how the ans is 588 :/
please explain me i can't under stand :(
Log in to reply
Where are you getting 777 = 334? The problem gives you the equation 7 3 = a 2 + b 2 and asks us to find a × b . In this case our n = 7. Using the above formula's for the general case we can find a = 28 and b = 21. And 2 8 × 2 1 = 5 8 8 .
The pattern is easy to discover. Each k th cube can be expressed by letting m 2 be the last term of the previous expression: k 3 = ( m + k ) 2 − m 2 . Extrapolating the pattern forwards we get: 5 3 = 1 5 2 − 1 0 2 , 6 3 = 2 1 2 − 1 5 2 , 7 3 = 2 8 2 − 2 1 2
2 8 × 2 1 = 5 8 8 which is our answer.
We prove the validity of this pattern by induction. Several bases have already been established in the question. Let us assume for some k , k 3 = m 2 − ( m − k ) 2 = ( 2 m − k ) ( k ) ⟹ 2 m − k = k 2 .
Adding 2 k + 1 to both sides we get:
2 m + k + 1 = ( k + 1 ) 2 ⟹ ( 2 m + k + 1 ) ( k + 1 ) = ( k + 1 ) 3 = ( m + k + 1 ) 2 − m 2
This completes the proof.
There are many ways of proving the validity of the conjecture.
Are there any other patterns that you notice in the sequence?
Were you referring to the triangular numbers series mentioned by David C below? I haven't met triangular numbers before...
From the pattern, we notice for n 3 , where n is a non-negative integer,
n 3 = a 2 - b 2 , where a and b are non-negative integers.
From the pattern, a = n + b. So, for the specific case where n = 7,
7 3 = ( 7 + b ) 2 - b 2
We manipulate this equation and solve for the unknown 'b' by expanding the right hand side of the equation.
343 = 49 + 14b + b 2 - b 2
294 = 14b
b = 21
a = 7 + b
a = 7 + 21
a = 28
a x b = 28 x 21
a x b = 588
∴ The answer is 588.
too long I think
The cube of the nth number is equal to the difference of the square of the nth triangular number and the square of the (n-1)th triangular number. Hence, 7 cubed equals 28 squared minus 21 squared. We can also write this shorthand as 7 3 = 2 8 2 − 2 1 2 . Therefore a and b are 28 and 21 respectively, and 2 8 ∗ 2 1 = 5 8 8
let: z 3 = x 2 − y 2 then z 3 = ( x + y ) ( x − y ) ⇒ z = ( x − y ) ( x + y ) ,
and let y = z ∗ α and x = y + z = z + z ∗ α
z = ( x − y ) ( x + y ) = ( z + z ∗ α − z ∗ α ) ( z + z ∗ α + z ∗ α )
z = z ( z + 2 ∗ z ∗ α )
α = ( 2 ∗ z ) ( z 2 − z )
then for 7 we've:
α = ( 2 ∗ 7 ) ( 7 2 − 7 ) = 3
x = y + 7 , y = α ∗ 7
x = 2 8 , y = 2 1
x ∗ y = 2 8 ∗ 2 1 = 5 8 8
I do not understand your first line. What is z = ( x − y ( x + y ) ? How did you reach that conclusion?
Can you also explain the pattern which you observed?
Log in to reply
my first time it's like Igor C (first part), also i see all z 3 = x 2 − y 2 implies z = x − y
so by letting x = α ∗ z + z and y = α ∗ z we've:
z 3 = ( x + y ) ( x − y )
z 3 = ( α ∗ z + z + α ∗ z ) ( α ∗ z + z − α ∗ z )
z 3 = ( z ( 2 α + 1 ) ) ( z )
z 3 = ( z 2 ( 2 α + 1 ) )
so:
z 2 z 3 = z = ( 2 α + 1 )
and
( x − y ) ( x + y ) = ( α ∗ z + z − α ∗ z ) ( α ∗ z + z + α ∗ z )
( x − y ) ( x + y ) = z z ( 2 α + 1 )
( x − y ) ( x + y ) = ( 2 α + 1 ) = z
α = 2 z − 1 = 2 ∗ z z 2 − z
this is my steps.
Log in to reply
It is not true that z 3 = x 2 − y 2 implies z = x − y in general. Though, what you likely meant, was that in the pattern we are given, we observe that z = x − y .
c 1 3 = ( c 2 ) 2 − ( c 2 − c 1 ) 2 , c 1 3 = ( 2 c 1 ( c 1 + 1 ) ) 2 − ( c 2 − c 1 ) 2 , 7 3 = ( 2 ( 7 ) ( 8 ) ) 2 − ( 2 ( 7 ) ( 8 ) ) − 7 ) 2 , 7 3 = ( 2 8 ) 2 − ( 2 1 ) 2 , a = 2 8 , b = 2 1 a × b = 2 8 × 2 1 = 5 8 8
7^3=(A-B)(A+B) A-B=7 A+B=49 2A=56 A=28 B=21 AB=28*21=588
the solution is: a= +2 +3 +4.... if 7 so that +7 that is 28 b= +1+2+3...... if 7 so that + 6 that is 21 28 * 21 = 588
1-3=2 3-6=3 6-10=-4 so next terms are 15 '21'28 by this 7cube is 28squre-21squre
using calculator f(x) es plus 991 - 7^3=x^2- a^2 the a in - 6^3= A^2 - b ^2= 21 the b is in - 5^3=10 which we got from 4^3 using that 7^3=x^2- 21^2 ans= 28 28 21=588
7^3=(a+b)(a-b)...a+b=7^2=49, a-b=7 solving we get a=28 b=21 axb=588
Note that this question asks you to recognize the pattern, as opposed to finding the values. As such, your solution is inaccurate.
Similar to your solution, we could have a + b = 7 3 = 3 4 3 , a − b = 1 which gives us a = 1 7 2 , b = 1 7 1 . However, this is not what we would have obtained from following the pattern.
Problem Loading...
Note Loading...
Set Loading...
We have this pattern:
So...
If a = 21 and b = 28, 28 * 21 = 558.